Investigating the effectiveness of protection motivation theory in predicting behaviors relating to natural disasters, in the households of southern Iran - Faryabi, Reza; Rezabeigi Davarani, Fatemeh; Daneshi, Salman; Moran, Declan Patrick (Frontiers in Public Health, 2023)
Background: Disasters can lead to large human casualties, destruction of property and economic and environmental resources. The purpose of the present study was to answer the question whether the Protection Motivation Theory (PMT) is effective in predicting behaviors related to the harmful effects of natural disasters in the households of southern Iran. Materials and methods: This quantitative and cross-sectional study was conducted on 528 households in Jiroft city. Sampling was done by combined method (the combination of cluster, simple random, proportional and systematic random sampling). A total of 528 households were included. The tools for collecting data were demographic information and a researcher-made questionnaire related to PMT constructs and preventive behaviors from the harmful effects of natural disasters. Data was analyzed using SPSS v21 software, and the necessary analyzes (descriptive tests, chi-square, one-way ANOVA and Pearson's correlation test) were performed at a significance level of 0.05. Using Amos v 21 software, the predictors of safety behaviors were determined using path analysis. Results: The results showed 51.7% lived in the city and 62.1% of residential buildings were of brick without markings. There is a significant difference between preventive behaviors and direct exposure to disasters (p<0.001), education (p=0.004), monthly income (p=0.004) and source of information (p=0.040). There was also a significant correlation between preventive behaviors and the number of vulnerable family members (p=0.001, r=0.160). The adjusted model of the path analysis test showed that protection motivation (β = 0.547), fear (β = 0.147) and perceived vulnerability (β = 0.135) had the greatest role among the constructs of the protection motivation theory. Conclusion: According to the results of the study, it is suggested that health planners design and implement educational interventions based on the structures of the mentioned model to increase the preparedness of households against natural disasters.